Spectrum of dermatophyte infections in Botswana - Thakur R (Dove Medical Press, 2015)
Rameshwari Thakur Department of Microbiology, Muzzaffarnagar Medical College, Uttar Pradesh, India Background: Dermatophyte infections are a common cause of superficial fungal infection in different geographical locations of the world. Usually, it involves superficial invasion of keratinized tissue, eg, skin, nails, and hair, but in immunosuppressed individuals, it may cause atypical, extensive and deep lesions, which may pose serious diagnostic and therapeutic challenges. Aim: To find out the causative dermatophyte species responsible for the various clinical types of dermatophyte infection. Results: Trichophyton violaceum was found to be the predominant species, being the causative organism responsible for all the clinical types. Conclusion: T. violaceum was found to be the most common species responsible for most of the clinical forms of dermatophytosis (96; 80%). Tinea unguium was found to be the most frequent clinical type of dermatophytosis (33; 27.50%). Keywords: Trichophyton violaceum, Trichophyton interdigitale, Trichophyton tonsurans, Trichophyton ferrugineum, tinea unguium, tinea corporis